Peningkatan Kemampuan Membaca Cepat melalui Media Cerita Bergambar Siswa Kelas Rendah MI Darul Ulum Bantaran Probolinggo - Nur Hayati; Yulina Fadilah (AS-SABIQUN, 2023)
The teacher at MI Darul Ulum in the teaching process is an effort to improve the reading ability of the students especially grade 1 students who have not used learning media used by the teacher at MI Darul Ulum to increase students readinthe media so that students can read fluently. So that the problems that occur in class 1 can be resolved, the researchernprovides a solution for using media in the teaching and learning process, an effort to improve students reading skills. As for the media used is pictorial story media, pictorial story media is visual media because it involves visualization. In using the illustrated story media, the researchers obtained the result of the reading ability of students in grade 1 MI Darul Ulum with 9 students. With an increase in learning mastery and students classical absorption is quite substansial from the two cycles that have been carried out. The indications are students who have completed the pre cycle namely 33%, in cycle I 44%, and 100% in cycle II, namely 20% in the pre cycle, 40% in the first cycle and 100% in the second cycle.